The neuroeconomics of mind reading and empathy - Tania Singer; Ernst Fehr (Institute for the Study of Labor (IZA), 2005)
The most fundamental solution concepts in Game Theory Nash equilibrium, backward induction, and iterated elimination of dominated strategies are based on the assumption that people are capable of predicting others' actions. These concepts require people to be able to view the game from the other players' perspectives, i.e. to understand others' motives and beliefs. Economists still know little about what enables people to put themselves into others' shoes and how this ability interacts with their own preferences and beliefs. Social neuroscience provides insights into the neural mechanism underlying our capacity to represent others' intentions, beliefs, and desires, referred to as Theory of Mind or mentalizing, and the capacity to share the feelings of others, referred to as empathy. We summarize the major findings about the neural basis of mentalizing and empathizing and discuss some implications for economics.
Keywords: A10; C90; 330; neuroeconomics; mind reading; empathy; Altruismus; Spieltheorie; Kognition; Neuroökonomie